Determination of al-Hajah and al-Darurah: An analysis from Juristic and Maqasid Study / Muhammad Mostofa Hossain - Muhammad Mostofa, Hossain (2024)
Some studies dispute the actual application of the concept of ḍarūrah and ḥājah to certain Islamic financial contracts. Despite there are claims that such application is in pursuit of maṣlaḥah, critics argue that the application fails to align with the essential criteria set by ḍarūrah and ḥājah not being entirely consistent with the underlying parameters (ḍawābiṭ). The study addresses the need for a precise alignment of the concept of ḍarūrah and ḥājah in attaining maṣlaḥah with the principles of maqāṣid al- Sharīʿah within the context of IBF. To deal with this issue, the study explores the Sharīʿah issues, scopes, and challenges associated with ḍarūrah and ḥājah, and their legal maxims in IBF, drawing upon both classical and contemporary Islamic jurisprudential scholarships and incorporating insights from interview analysis. To carry out the outcomes, the study adopts a qualitative research approach, utilising descriptive and analytical methods. In addition to reviewing relevant works of literature through library works and document analysis, the research conducts semi-structured interviews with Sharīʿah advisors, academicians, Sharīʿah researchers and Sharīʿah consultants. The findings from the study and interviews reveal several reasons contributing to the misapplication of ḍarūrah and ḥājah in IBF. These factors include but are not limited to overlooking parameters and conditions, not adequately addressing the spirit of ḍarūrah and ḥājah, prioritising profit maximisation, a lack of comprehensive understanding and the absence of a unified framework for product development. In response to these challenges, the study proposes a novel framework for product development tailored to the global IBF industry, accompanied by a set of recommendations to enhance the alignment of ḍarūrah and ḥājah within the IBF.